THE EFFECT OF PERFORMANCE APPRAISAL ERRORS ON EMPLOYEE PERFORMANCES: AN EXAMINATION IN INDUSTRIAL COOLING MANAGEMENTS IN TURKEY IN TERMS OF EMPLOYEE PERCEPTIONS - Erbasi, Ali; Arat, Tugay; Buyukipekci, Semih (European Scientific Journal, ESJ, 2012)
The purpose of this study is to examine the effect of performance appraisal errors faced by industrial cooling managements on personal performances in terms of employee perceptions. Besides, the attitudes towards work performances of the employees and performance appraisal errors are also studied to see if there is any difference in terms of several demographical characteristics. The questionnaires prepared for this purpose are applied to 200 people that work in 14 industrial cooling managements currently operating in Central Anatolian Region in Turkey. There are 39 hypotheses obtained from these questionnaires. According to the findings of the study, the most common error faced by industrial cooling managements is the halo effect, and the least one is that the relations among different works are not considered with full attention. In accordance with the results of the study, 9 of the employee perceptions in terms of performance appraisal error have a negative effect on work performance, though 15 of the employee perceptions in terms of performance appraisal error have no effect on work performance. Moreover, there is a significant difference in the attitudes of employees in terms of performance appraisal errors according to the income level, education status and the frequency of performance appraisal required to apply within the management. Besides these, the perception of employees on performance levels has a significant difference according to the performance management, education status, and the participation towards the efficiency and effectiveness of performance appraisal and the frequency of performance appraisal presumed to be in use within the management. The results obtained from the study indicate significant data for strategic management personnel in industrial cooling managements.